PENGARUH MODEL PEMBELAJARAN KOOPERATIF BERBASIS PEMBERDAYAAN BERPIKIR TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEMAMPUAN AKADEMIK SISWA - Septiana Dwi Utami; Jamaluddin Jamaluddin; Nyoman Sridana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2014)
This study aims to find out: 1) the influence of application of cooperative learning model based on empowerment of thinking (PKBPB) to the learning outcomes of science; 2) the influence of academic ability on science learning outcomes; and 3) the influence of PKBPB model interaction with academic ability on science learning outcomes. This study uses a population sample consisting of 98 students from 4 classes. This research is a quasi-experimental research using factorial design 2 x 2. Data collection is done by test. Data were analyzed using covariance analysis with the help of SPSS 18 for windows program. The result of data analysis shows that: 1) there is influence of PKBPB model implementation toward science learning result (F = 6.065 and p <0.05); 2) there is influence of students' academic ability on science learning outcomes (F = 6.171 and p <0.05); and 3) there is no interaction between PKBPB and non PKBPB model with academic ability on science learning outcomes (F = 0.486 and p = 0.487).